Penal Provisions for Crimes of Discrimination and Hate Speech in Algerian Legislation within Law 20-05 - Khaled DOU (Social Empowerment Journal, 2021)
This research studies the crimes of discrimination and hate speech that stipulated by the Algerian legislator in Law 20-05 issued on April 28, 2020, and determined its punishments in this law. The research aims to define the racial discrimination, hate speech, and explain its forms and the reasons for its criminalization, and the efforts of the Algerian legislator in an attempt to reduce the spread of this phenomenon. It also aims to classifying crimes of discrimination and hate speech and stating its punishments by analyzing some articles from Law 20-05 related to its, and clarifying the exceptional cases that Algerian legislation considered in these crimes; either in toughening or reducing. One of the most important results of the research is that discrimination is every distinction or exception in rights and freedoms; it based on color, lineage, language, belonging, or health status. Hate speech is any expression that suggests discrimination and provokes hatred between the people, whatever its form. The Algerian legislator has addressed this phenomenon by issuing a law to prevent discrimination and hate speech in the year 2020, it contains the punishments of the discrimination, and the participation in it, and encouragement for it, as well contains exceptional cases; some of it have toughening the punishment, some reduce it, and some exempt the offender from punishment.